Microwave digestion for determination of iron and zinc content of total food - Silva-Trejos, Paulina (2012)
In this study, the procedure was optimized digestion of food by means of a microwave oven, to quantify the total iron and zinc in different matrices by atomic absorption spectroscopy. We analyzed the optimal amount of 65% concentrated HNO3 to digest sample mass determined by evaluating the percent recover y obtained with different amounts of HNO3.The results are similar to those obtained by the methods recommended officially acid digestion in open systems and calcination.